2016
DOI: 10.1111/ajag.12305
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the implementation ofposlansia, Indonesia's community-based health programme for older people

Abstract: The findings indicate existing support from the community, community health centres and related institutions for poslansia is not adequate for optimal service function. Health awareness among the older population should also be increased for programme sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Currently, there are fewer HCPs working in rural areas compared to urban centres. Moreover, given the geographical distance of the rural service centres from the cities, laywomen as well as Kader provide services with little supervision or input from professionals [29]. Consequently, care tends to be suboptimal and largely focused on just providing medication; little attention is given to prevention and health promotion [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are fewer HCPs working in rural areas compared to urban centres. Moreover, given the geographical distance of the rural service centres from the cities, laywomen as well as Kader provide services with little supervision or input from professionals [29]. Consequently, care tends to be suboptimal and largely focused on just providing medication; little attention is given to prevention and health promotion [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given the geographical distance of the rural service centres from the cities, laywomen as well as Kader provide services with little supervision or input from professionals [29]. Consequently, care tends to be suboptimal and largely focused on just providing medication; little attention is given to prevention and health promotion [29]. Therefore, more education, training, and supervision of laywomen and Kader are needed to improve the quality of service delivered in smaller, rural communities [29].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the insufficient financial resources for posyandu was the bottleneck leading to other problems faced by posyandu, such as problems in medicine, equipment supplies, lack of CHW's capacity (related to inadequate training), and infrastructure. The problems found to be similar with posyandu's for other health program, and may, in turn, lead to ineffective program's implementation (Christiani, Byles, Tavener, & Dugdale, 2016).…”
Section: Discussionmentioning
confidence: 70%
“…The Indonesian Ministry of Health has developed NCDs control programs and launched several community health centers (Puskesmas) and health village posts for older adults (Posyandu Lansia) in the mid-2000s. Current activities at Posyandu Lansia are mostly focused on disease and risk factor screening, such as blood pressure (BP) or body weight measurement, while a few also implement activities related to disease prevention, health promotion, and social engagement [9]. Many studies have reported the rapid increase of NCDs, but there has been only a little research on how the community may be involved in the successful management of NCDs [10].…”
Section: Introductionmentioning
confidence: 99%